2016
DOI: 10.19082/3170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of postoperative pressure ulcer: A systematic meta-analytic review

Abstract: IntroductionA pressure ulcer is a serious safety issue in healthcare systems. The patient’s rate of infection with an ulcer, especially a postoperative ulcer, is critical, as it is dictated by factors such as being in a fixed position during surgery, the type of anesthesia used, the duration of surgery, and patient-related factors. The present study was conducted to carry out a systematic assessment of the prevalence of a postoperative pressure ulcer and to find its general prevalence using a meta-analysis.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 20 publications
6
28
1
6
Order By: Relevance
“…Our study found low BMI and low preoperative Braden score to be significant predictors of HAPU, which is consistent with other similar studies . However, there are also studies that identified the postoperative Braden score as a significant predictor of HAPU . Therefore, we performed an additional secondary analysis on the postoperative Braden score and found that it was also statistically significant in our univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study found low BMI and low preoperative Braden score to be significant predictors of HAPU, which is consistent with other similar studies . However, there are also studies that identified the postoperative Braden score as a significant predictor of HAPU . Therefore, we performed an additional secondary analysis on the postoperative Braden score and found that it was also statistically significant in our univariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…7,12,21,24 However, there are also studies that identified the postoperative Braden score as a significant predictor of HAPU. 33,34,41 Therefore, we performed an additional secondary analysis on the postoperative Braden score and found that it was also statistically significant in our univariate analysis. However, we did not include it in our prediction model because we wanted to use variables that are available preoperatively to determine a patient's pressure ulcer risk.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…A better understanding of the risk factors for PI is essential as it may allow stratification of patients before surgery, and targeted prevention. Here, it was a surprise to find that sex was not associated with the development of PI, as a previous meta‐analysis has reported this. A large number of studies were included in the present meta‐analysis of sex, and it is unlikely that an increased risk could have been missed.…”
Section: Discussionmentioning
confidence: 69%